IMPLEMENTASI DATA MINING UNTUK MEMPREDIKSI KINERJA KERJA KARYAWAN MENGGUNAKAN METODE REGRESI LINIER BERGANDA - Juni Kristian Gea; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2022)
Utilization of technology in the field of data, especially in predicting the work performance of employees at PT. Mandiri Karya Nusantara is very lacking so that it can result in a decrease in the quality of the company to compete in the business world. This study aims to: (1) to analyze the application of data mining to employee assessments in predicting employee performance at PT. Mandiri Karya Nusantara (2) to apply the multiple linear regression method in predicting the work performance of employees at PT. Mandiri Karya Nusantara. This research is a research that takes data mining from 133 employee performance data of PT. Mandiri Karya Nusantara. This research uses Multiple Linear Regression method. The calculation results obtained 358 prediction results, so it can be predicted that employee performance increased by 358 from the previous period and in the following period. Prediction of the increase is supported by the results of analysis with multiple linear regression using SPSS which is known that the significance value is 0.000 <0.05, which means that there is an influence of discipline, skills, work productivity and work quality on employee performance. The application of the employee performance analysis can be used to improve the variables that influence the increase in employee performance. So it is necessary to pay attention to employee discipline, skills / abilities, work productivity, and work quality on employee performance.